Improving Nutritional Value of Cow Manure with Biomass Ash and Its Response to the Growth and K-Ca Absorption of Mustard on Inceptisols. Issue 1 (April 2021) - Hanudin, E; Iskyati, W; Yuwono, N W
Abstract: Cow manure is widely used by Indonesia vegetable farmers but the nutrients content is relatively low (paticularly for K and Ca). Wood and husk ash as a by-products from the pottery burning process are widely available in the villages and have not been fully utilized. The ash is rich in K and Ca nutrients, so it is useful for increasing the nutritional value of cow manure. This study was aimed to determine the effect of enricment cow manure (ECM) on soil chemical properties, growth and K-Ca uptaken by mustard on Inceptisols. The green house experiment conducted by using 5 kg of soil, with a completely randomized design. As treatment 1: Mixed cow manure (CM)+Husk Ash (HA) with doses of 0+100, 900+100, 925+75, 950+50, 975+25 g/pot); Treatment 2: CM+Wood Ash mixture (WA) with the same dose. While there are 3 controls, namely: soil without fertilizer, soil + CM 1000 g/pot, and soil + CM 123 g/pot. The results showed that ECM significantly increased the soil fertility and plant growth. The highest K and Ca uptake in the shoot was obtained at CM + HA treatment with dose of 925 + 75 and 900 + 100 g/pot, respectively. This research is part of a step towards grounding the organic agriculture concept, so there is still an opportunity to research other materials as materials for manure fortification.